FeSe(2)-Decorated Bi(2)Se(3) Nanosheets Fabricated via Cation Exchange for Chelator-Free (64)Cu-labeling and Multimodal Image-Guided Photothermal-Radiation Therapy - Cheng, Liang (Adv Funct Mater, 2016)
Multifunctional theranostic agents have become rather attractive to realize image-guided combination cancer therapy. Herein, we develop a novel method to synthesize Bi(2)Se(3) nanosheets decorated with mono-dispersed FeSe(2) nanoparticles (FeSe(2)/Bi(2)Se(3)) for tetra-modal image-guided combined photothermal & radiation tumor therapy. Interestingly, upon addition of Bi(NO(3))(3), pre-made FeSe(2) nanoparticles via cation exchange would be gradually converted into Bi(2)Se(3) nanosheets, on which remaining FeSe(2) nanoparticles are decorated. The yielded FeSe(2)/Bi(2)Se(3) composite-nanostructures were then modified with polyethylene glycol (PEG). Taking advantages of the high r(2) relaxivity of FeSe(2), the X-ray attenuation ability of Bi(2)Se(3), the strong near-infrared (NIR) optical absorbance of the whole nanostructure, as well as the chelate-free radiolabeling of (64)Cu on FeSe(2)/Bi(2)Se(3)-PEG, in vivo magnetic resonance (MR)/computer tomography (CT)/photoacoustic (PA)/position emission tomography (PET) multimodal imaging was carried out, revealing efficient tumor homing of FeSe(2)/Bi(2)Se(3)-PEG after intravenous injection. Utilizing the intrinsic physical properties of FeSe(2)/Bi(2)Se(3)-PEG, in vivo photothermal & radiation therapy to achieve synergistic tumor destruction was then realized, without causing obvious toxicity to the treated animals. Our work presents a unique method to synthesize composite-nanostructures with highly integrated functionalities, promising not only for nano-biomedicine, but also potentially for other different nanotechnology fields.